Evaluating Bone Health in Egyptian Children with Forearm Fractures: A Case Control Study - Abeer El-Sakka; Cristina Penon; Adham Hegazy; Salwa Elbatrawy; Amr Gobashy; Alvaro Moreira (Hindawi Limited, 2016)
Objective. To determine the likelihood of vitamin D deficiency and low bone mineral density in Egyptian children with forearm fractures. Methods. A case control study of 46 children aged 3 to 10 years with or without forearm fractures. Validated questionnaires were used to assess calcium and vitamin D intake as well as sun exposure. Serum calcium, phosphorus, alkaline phosphatase, and 25-hydroxy-vitamin D were collected. Bone mineral density was evaluated using dual-energy X-ray absorptiometry. Results. Compared to the Control group, calcium and vitamin D intake was lower in the Cases group (p=0.03). Cases had higher Body Mass Index than Controls, p=0.01. Children in the Cases group had lower mean serum calcium values 8.3±1.4 compared to 9.3±1.1 in Controls (p=0.01). Alkaline phosphatase was higher in Cases 265±65.8 than Controls 226±54.6 (p=0.03). Vitamin D and bone mineral density scores were significantly lower in the Cases group (p<0.05). Conclusion. Our data shows an increased rate of vitamin D deficiency and decreased bone mineral density in Egyptian children with forearm fractures.